A Cross-Reactive Human Single-Chain Antibody for Detection of Major Fish Allergens, Parvalbumins, and Identification of a Major IgE-Binding Epitope. - Merima Bublin; Maria Kostadinova; Julian E Fuchs; Daniela Ackerbauer; Adolfo H Moraes; Fabio C L Almeida; Nina Lengger; Christine Hafner; Christof Ebner; Christian Radauer; Klaus R Liedl; Ana Paula Valente; et al. (PLoS ONE, 2015)
Fish allergy is associated with moderate to severe IgE-mediated reactions to the calcium binding parvalbumins present in fish muscle. Allergy to multiple fish species is caused by parvalbumin-specific cross-reactive IgE recognizing conserved epitopes. In this study, we aimed to produce cross-reactive single chain variable fragment (scFv) antibodies for the detection of parvalbumins in fish extracts and the identification of IgE epitopes. Parvalbumin-specific phage clones were isolated from the human ETH-2 phage display library by three rounds of biopanning either against cod parvalbumin or by sequential biopanning against cod (Gad m 1), carp (Cyp c 1) and rainbow trout (Onc m 1) parvalbumins. While biopanning against Gad m 1 resulted in the selection of clones specific exclusively for Gad m 1, the second approach resulted in the selection of clones cross-reacting with all three parvalbumins. Two clones, scFv-gco9 recognizing all three parvalbumins, and scFv-goo8 recognizing only Gad m 1 were expressed in the E. coli non-suppressor strain HB2151 and purified from the periplasm. scFv-gco9 showed highly selective binding to parvalbumins in processed fish products such as breaded cod sticks, fried carp and smoked trout in Western blots. In addition, the scFv-gco9-AP produced as alkaline phosphatase fusion protein, allowed a single-step detection of the parvalbumins. In competitive ELISA, scFv-gco9 was able to inhibit binding of IgE from fish allergic patients' sera to all three β-parvalbumins by up to 80%, whereas inhibition by scFv-goo8 was up to 20%. 1H/15N HSQC NMR analysis of the rGad m 1:scFv-gco9 complex showed participation of amino acid residues conserved among these three parvalbumins explaining their cross-reactivity on a molecular level. In this study, we have demonstrated an approach for the selection of cross-reactive parvalbumin-specific antibodies that can be used for allergen detection and for mapping of conserved epitopes.